The Autosomal Recessive Inheritance of Hereditary Gingival Fibromatosis - Poulami Majumder; Vineet Nair; Malancha Mukherjee; Sujoy Ghosh; Subrata Kumar Dey (Hindawi Limited, 2013)
Hereditary gingival fibromatosis (HGF) is a rare condition which is marked by enlargement of gingival tissue that covers teeth to various extents leading to aesthetic disfigurement. This study presents a case of a 28-year-old female patient and 18-year-old male who belong to the same family suffering from HGF with chief complaint of overgrowing swelling gingiva. The presence of enlarged gingiva with the same eruption was found in their other family members with no concomitant drug or medical history, and the occurrence of HGF has been found in one generation of this family which may indicate the autosomal recessive inheritance pattern of HGF. Hereditary gingival fibromatosis is an idiopathic condition as its etiology is unknown and it was found to recur in some cases even after surgical treatment. Both patients underwent thorough oral prophylaxis and later surgical therapy to correct the deformity.